Model Of Islamic Education Development In Papua Muslim Minority - Nasrul Fauzi; Muhammad Averoos Azzam Al Islami (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study examines the role and challenges in developing Islamic education in the Muslim minority in the remote areas of Tambrauw Regency, West Papua. This research is field research. The data used is qualitative in the form of words and descriptions. Data was collected by using literature, observation, and interview methods. Comments are made to order data that can be sensed directly, such as the location and activities of Islamic education. Meanwhile, interviews were conducted to collect data on the role, challenges, and patterns of developing Islamic education. This study found that the part of MUI, PCNU, and the Tambrauw Regional Government in Islamic education is establishing and developing Islamic education, including financial support and teaching staff. At the same time, the challenge consists of 2 parts, namely the past difficulties related to the conflict of belief migration carried out by several Abun tribal communities by the officers and Christian religious leaders at that time. The current challenge is the lack of existing facilities, facilities, and infrastructure and the lack of adequate teaching staff. The pattern used in the development of Islamic education in Tambrauw is by establishing an Islamic Elementary School, establishing an Al-Quran Education Park and the Taksim Council, establishing Bible Studies, and sending the indigenous Abun and Moi Karon Muslims to various Islamic boarding schools outside Papua for deepening the religion of Islam as a candidate for Islamic driving cadres in the future.